Effects of Different Weekly Set Volumes on Strength and Perceptual Responses in Athletes - Enes, Alysson; Spiess, Bruno; Oneda, Gustavo; Leonel, Danilo Fonseca; Bernardo, Mauro F.; Macedo, Ana Carolina G.; Alves, Ragami Chaves; De Souza, Eduardo Oliveira; Souza-Junior, Tácito P. (International Journal of Sports Medicine, 2024)
This study investigated the effects of different resistance training (RT) volumes quantified by weekly sets at high intensity (load and effort) on dynamic strength adaptations and psychophysiological responses in trained individuals. Twenty-four athletes were randomly allocated to three groups that performed three (3 S, n=8), six (6 S, n=8), and nine (9 S, n=8) weekly sets, respectively, three times a week on the barbell back squat and bench press during an 8-week period. While all groups showcased strength gains (p<0.05), post hoc comparisons revealed that 6 S and 9 S elicited greater strength adaptations than 3 S in barbell back squat (p=0.027 and p=0.004, respectively) and bench press (p=0.001 and p=0.044, respectively). There were no differences between 6 S and 9 S conditions for back squat (p=0.999) and bench press (p=0.378). Although a time effect was observed for Session-RPE (p=0.014) and Total Quality Recovery scale (p=0.020), psychophysiological responses were similar among groups. Our findings suggest that performing six and nine weekly sets at high intensities led to greater strength gains compared to three weekly sets in strength-trained individuals, despite similar psychophysiological responses.
Keywords: muscle strength; squat; bench press; rating of perceived exertion; total training volume